A comparative study of modal dispersion characteristics of different types of concave-lens-shaped dielectric waveguides - Kumar N.; Srivastava S.K.; Ojha S.P. (My University, 2025)
In this paper, we present a comparative study of different types of concave lens-shaped dielectric waveguides and a dielectric square waveguide. Using the point-matching technique under the weak-guidance approximation, a general characteristic equation has been derived and modal dispersion curves are obtained and interpreted. This waveguide cross section may be considered as a distortion of the square waveguide with a transverse compression at one pair of parallel sides in order to form the concave lens shape. Some important insights have been drawn about the comparison of their dispersion curves. It is observed that the cutoff value of the lowest order mode (Vc) increases with an increase in compression depth.